Hubungan Pola Makan dan Kelengkapan Imunisasi Terhadap Kejadian Stunting di Desa Tanjung Gunung - Syafitri, Ririn; Agustin, Agustin (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2025)
Stunting remains a crucial issue during the golden age. In the Bangka Belitung Islands Province, stunting has only decreased by 0.005% despite the region being rich in nutritious marine resources such as fish. One of the affected areas is Tanjung Gunung Village. Low utilization of local food potential and inadequate immunization coverage are contributing factors to the high stunting rate. Immunization plays a crucial role in preventing infections that cause malnutrition. This study aims to determine the relationship between dietary patterns and immunization coverage with stunting incidence in Tanjung Gunung Village. This study is an observational analytical quantitative study using a case-control method to determine the relationship between independent and dependent variables. The sample size was 21 toddlers with stunting (cases) and 21 toddlers without stunting (controls) using a purposive sampling technique. Using the chi-square test with a 95% confidence level (? = 0.05). The results of this study, found a relationship between dietary patterns (p = 0.000; OR = 0.020), completeness of immunization (p = 0.000; OR = 0.018) and the incidence of stunting in Tanjung Gunung village. Conclusion: This study found that completeness of basic immunizations was the most influential factor in stunting among toddlers in Tanjung Gunung Village. These findings are supported by various scientific journals showing that complete basic immunization plays a crucial role in reducing the risk of stunting in toddlers, through protection against infectious diseases that can disrupt a child's growth process and nutritional status.